Deciphering the Effect of Postharvest 1-MCP Treatment Coupled with Low-Temperature Storage on the Physiological Activities and Edible Quality of Melon - Haofei Wang; Zhiyi Yang; Sikandar Amanullah; Huilin Wang; Bin Liu; Shi Liu; Tiantian Yang; Chaonan Wang (Plants)
Fruits are an important source of a healthy diet due to their essential nutrients for daily intake. Melon is known as a significant fruit crop of the Cucurbitaceae family based on its various dietary benefits, but its shelf life needs to be maintained for long-term usage. 1-Methylcyclopropene (1-MCP) is a cyclopropene-derived synthetic plant growth regulator (PGR) that is used for significantly delaying the ripening process and maintaining the shelf life of climacteric fruits during storage. In this study, freshly harvested melon fruits were fumigated with various concentrations (1.0 µL·L−1, 2.0 µL·L−1, and 3.0 µL·L−1) of 1-MCP treatment for 12 h (h) and stored at low temperature (8 ± 1 °C) for 30 days (d). The obtained results showed that 1-MCP fumigation coupled with low-temperature treatment maintains the postharvest shelf life of melon fruit. It was noticed that the increase in color hue (a* (red/green), b* (blue/yellow), L* (lightness)) was slowed down and the external fresh color was effectively maintained. At the same time, the firmness, soluble solids, titratable acids (TAs), and vitamin C (VC) content seemed to be maintained at a high level; weight loss and cell permeability were reduced; respiratory intensity and ethylene emission were inhibited; and the accumulation of superoxide anions and malondialdehyde (MDA) was also reduced. In addition, an upsurge in the activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) was noticed in melon fruits under the combined treatment of 1-MCP and low-temperature storage as compared with the control group (CK, without treatment), indicating that 1-MCP treatment can effectively enhance the antioxidant metabolism of melon fruits during storage. Overall, we can recommend that the 3.0 µL·L−1 concentration of 1-MCP had the best effect on maintaining the internal and external quality of sweet melon fruit during storage.